Analisis Beban Kerja Untuk Perencanaan Kebutuhan Sumber Daya Manusia (SDM) Bidang Bina Marga Dinas Pekerjaan Umum Dan Penataan Ruang (PUPR) Kabupaten Lombok Barat - Rahmat Hidayat; Agusdin Agusdin; Dwi Putra Buana Sakti (Master of Management, Mataram University, 2018)
This study aims to analyze the workload of each work unit and HR category, analyze the needs of the number and competency of HR and analyze the investment costs of procurement and compensation for HR needs in the Highways Division of the PUPR Office of West Lombok Regency. The population in this study were all employees who worked in the Highways Division of the PUPR Office of West Lombok Regency totaling 39 people. Census method as a data collection method used. The data analysis technique used in this study is WISN (Workload Indicators of Staffing Need). The results showed that the workload in each unit of Bina Marga was still not optimal, the Marga field still lacked 10 employees and still needed competency improvement, the results of the analysis also showed the type of procurement that must be carried out by the Highways Division with compensation costs in accordance with applicable guidelinesKeywords:Workload, Human Resource Planning, Human Resource Needs, Workload Indicators of Staffing Need, Business Management